Merkel cell carcinoma occurring in a black woman: a case report - Kadiri, Selma (J Med Case Rep, 2017)
BACKGROUND: Merkel cell carcinoma is a rare, very aggressive neuroectodermal tumor of the skin. It is typically located on sun-exposed skin and frequently found in white men aged between 70 and 80 years. CASE PRESENTATION: We report a case of a 58-year-old black woman diagnosed with Merkel cell carcinoma of the posterior face of the right elbow. She had biopsy excision and was lost to follow-up. Four months later, she presented with recurrent disease on the inferior third of the right arm with three ipsilateral axillary lymph node metastases. Amputation of the right arm and ipsilateral axillary lymph node dissection were performed, followed by adjuvant radiotherapy. Six months later, the patient died as a result of respiratory failure caused by lung metastasis. To the best of our knowledge, no specific studies have been done comparing the course and the characteristics of Merkel cell carcinoma in white and black populations, and no similar case has been reported in the literature. CONCLUSIONS: The Merkel cell carcinoma is very rare in black people. As described elsewhere in the literature, our patient had a poor outcome despite radical management. To date, to the best of our knowledge, there has been no comparison of the prognosis of this tumor in white and black populations.